Experimental study on the cyclic variations of ethanol/diesel reactivity controlled compression ignition (RCCI) combustion in a heavy-duty diesel engine. (15th December 2021) - Pan, Suozhu; Cai, Kai; Cai, Min; Du, Chenbo; Li, Xin; Han, Weiqiang; Wang, Xin; Liu, Daming; Wei, Jiangjun; Fang, Jia; Bao, Xiuchao
Abstract: The current work was performed to study the cyclic variations of ethanol/diesel reactivity controlled compression ignition (RCCI) combustion on a heavy-duty diesel engine. The effects of diesel injection timing and premixed ratio (PR) on the cyclic variations were researched. Several parameters such as the maximum in-cylinder pressure (Pmax ), the maximum heat release rate (HRRmax ), the maximum pressure rise rate (PRRmax ) and the indicated mean effective pressure (IMEP) were employed to evaluate the cyclic variations by using the coefficient of variation (COV) of each parameter. The results show that the cyclic variations of ethanol/diesel RCCI combustion are sensitive to the diesel injection timing and PR. with advance of diesel injection timing, the COVs of all parameters decrease at first and then increase, the frequency distribution of all parameters firstly becomes more concentrated and then gets more dispersed, the distribution ranges of the crank angle of Pmax, HRRmax, PRRmax are narrowed firstly and then widened. With increment of PR, the COVs of all parameters firstly decrease and then increase, the frequency distribution of all parameters firstly becomes more concentrated and then gets more dispersed. The results of this work reveal that diesel injection timing and PR should be optimized to achieve smaller cyclic variation and more smooth operation of ethanol/diesel RCCI engine. Highlights: The cyclic variations of ethanol/diesel RCCI combustion mode were investigated. The coefficients of variation of several main parameters were analyzed. The cyclic variations of ethanol/diesel RCCI are sensitive to the diesel injection timing and PR. COVs of all parameters decrease at first and then increase with advance of diesel injection timing. COVs of all parameters firstly decrease and then increase with increment of PR.